Rhizoremediation – A promising tool for the removal of soil contaminants: A review. Issue 2 (April 2020) - Saravanan, A.; Jeevanantham, S; Narayanan, V. Anantha; Kumar, P. Senthil; Yaashikaa, P.R; Muthu, C.M Mathan
Graphical abstract: Abstract: Over most recent couple of decades, the contamination of water and soil has turned into a remarkable risk to biological community and human health. Plant-based remediation of contaminants is a reasonable method to battle the terrible truth of defilement. Rhizoremediation, a particular sort of phytoremediation that includes the two plants and their related rhizosphere microorganisms, can happen normally, or can be impelled by intentionally presenting explicit organisms. Since it is a plant situated in-situ phytorestoration system it is turned out to be conservative, productive and simple to actualize under field conditions. Though there are several remediation processes already exist, they failed to degrade the contaminants completely. During the rhizoremediation process, the plant roots secreted the exudates which will enhance or stimulates the growth and activity of microbial community in the rhizosphere. This results in effective degradation of pollutants. The plant root arrangement will spread the microbes through the soil and also helps to permeate even in the impermeable soil layers. Due to its advantages this might be effective in the future for the degradation of contaminants. The vaccination of contamination debasing microorganisms on plant seed can be a critical added substance to improve the productivity of phytoremediation or bioaugmentation. Determination of right microorganisms and vaccination to seed foundations of appropriate plant species will broaden the points of view of rhizoremediation.